Incidence and predictors of in-hospital non-cardiac death in patients with acute heart failure. Issue 5 (August 2017) - Wakabayashi, Kohei; Sato, Naoki; Kajimoto, Katsuya; Minami, Yuichiro; Mizuno, Masayuki; Keida, Takehiko; Asai, Kuniya; Munakata, Ryo; Murai, Koji; Sakata, Yasushi; Suzuki, Hiroshi; Takano, Teruo; et al.
Background: Patients with acute heart failure (AHF) commonly have multiple co-morbidities, and some of these patients die in the hospital from causes other than aggravated heart failure. However, limited information is available on the mode of death in patients with AHF. Therefore, the present study was performed to determine the incidence and predictors of in-hospital non-cardiac death in patients with AHF, using the Acute Decompensated Heart Failure Syndromes (ATTEND) registry Methods: The ATTEND registry included 4842 consecutive patients with AHF admitted between April 2007–September 2011. The primary endpoint of the present study was in-hospital non-cardiac death. A stepwise regression model was used to identify the predictors of in-hospital non-cardiac death. Results: The incidence of all-cause in-hospital mortality was 6.4% ( n =312), and the incidence was 1.9% ( n =93) and 4.5% ( n =219) for non-cardiac and cardiac causes, respectively. Old age was associated with in-hospital non-cardiac death, with a 42% increase in the risk per decade (odds 1.42, p =0.004). Additionally, co-morbidities including chronic obstructive pulmonary disease (odds 1.98, p =0.034) and anaemia (odds 1.17 (per 1.0 g/dl decrease), p =0.006) were strongly associated with in-hospital non-cardiac death. Moreover, other predictors included low serum sodium levels (odds 1.05 (per 1.0 mEq/l decrease), p =0.045), high C-reactive protein levels (odds 1.07, p <0.001) and no statin use (odds 0.40, p =0.024). Conclusions: The incidence of in-hospital non-cardiac death was markedly high in patients with AHF, accounting for 30% of all in-hospital deaths in the ATTEND registry. Thus, the prevention and management of non-cardiac complications are vital to prevent acute-phase mortality in patients with AHF, especially those with predictors of in-hospital non-cardiac death.